Interpreter Chart Diagram N-S - Mac Gaul de Jorge, Marcia (2009)
The team of researchers develops and implements technological resources focused on a methodological strategy that supports its use. Our investigation deals with the analysis beginner students’ competences attending the Analisis de Sistema career at the UNSa, in order to solve different computing problems such as the analysis of the design if the diagram N-S and the desktop test. This work describes the process undertaken by the educational software design called Diagramar. Its development and the searching activity are related to the adopted methodologies: the Extreme Programming and Investigation-Action. The pedagogical importance of Diagramar lies on finding an answer to students and teachers’ needs, providing a technological resource developed to fit these needs. It is mainly focused on the elaboration of the N-S diagrams. There are not many texts that provide an specification of algorithm and translate a methodological strategy able to support the staff of teachers from a continual investigation on its own practice.